Review of feedback in edutainment games for preschoolers in the USA. Issue 3 (3rd July 2021) - Nikolayev, Mariya; Reich, Stephanie M.; Muskat, Tallin; Tadjbakhsh, Nazanin; Callaghan, Melissa N.
ABSTRACT: Feedback is an essential component of children's learning; yet, how it is provided through the edutainment market for preschoolers is largely understudied. This study examined the prevalence and patterns of different types of positive and negative verbal and non-verbal feedback in 76 digital games produced by three popular US networks. Fifteen types of feedback were distinguished: nine types in response to incorrect actions and six types in response to correct actions. Although most games offered feedback, very few provided the types of feedback known to promote learning. Specifically, games relied on simple non-specific verification to indicate whether players' actions were right or wrong and missed opportunities to use elaborative and scaffolded feedback to help players understand why an action was correct or incorrect. Additionally, games seldom missed an opportunity to provide positive feedback but often omitted negative feedback. Finally, games used repeated instructions but not positive feedback to motivate game-play. Focusing on a diversity of types of games (from math to art) available on web- and/or mobile platforms, we find a disconnect between design features associated with children's learning and the actual design of edutainment for young children.